PENGGUNAAN NAVIGASI BINTANG DI ALAM BEBAS PADA MALAM HARI DALAM PENENTUAN ARAH KIBLAT - Samsudin samsudin; Ubaidillah Ubaidillah; Masriah Masriah (IAIN Syekh Nurjati Cirebon, 2019)
AbstractIn conditions in the wild we often have difficulty in determining the direction, especially if we do not carry a pointing device such as a compass, therefore the position of heavenly bodies can be relied upon. The existence of celestial objects can be a navigation instrument that becomes a reference in determining the direction of the Qibla by observing the position of the star, this study was conducted to prove whether the position of a star can be used as a natural tool other than the sun in determining the Qibla direction.This study aims to answer the questions that formulate the problem: